Exploring the utility of ultrasound to assess disuse atrophy in different muscles of the lower leg - Edward J. Hardy; Joseph J. Bass; Thomas B. Inns; Mathew Piasecki; Jessica Piasecki; Craig Sale; Robert H. Morris; Jonathan N. Lund; Ken Smith; Daniel J. Wilkinson; Philip J. Atherton; Bethan E. Phillips (Journal of Cachexia, Sarcopenia and Muscle)
Abstract Background Skeletal muscle is a highly plastic tissue crucial for many functions associated with whole‐body health across the life course. Magnetic resonance imaging (MRI) is the current gold standard for measuring skeletal muscle size. However, MRI is expensive, and access to facilities is often limited. B‐mode ultrasonography (U/S) has been proposed as a potential alternative to MRI for the assessment of muscle size. However, to date, no work has explored the utility of U/S to assess disuse muscle atrophy (DMA) across muscles with different atrophy susceptibility profiles, an omission which may limit the clinical application of previous work. Methods To address this significant knowledge gap, 10 young men (22 ±  years, 24.1 ± 2.3 kg/m2) underwent 15‐day unilateral leg immobilization using a knee‐brace and air boot. Cross‐sectional area (CSA) and muscle thickness (MT) of the tibialis anterior (TA) and medial gastrocnemius (MG) were assessed via U/S before and after immobilization, with CSA and muscle volume assessed via MRI. Results With both muscles combined, there were good correlations between each U/S and MRI measure, both before (e.g., CSAMRI vs. MTU/S and CSAU/S: r = 0.88 and 0.94, respectively, both P < 0.0001) and after (e.g., VOLMRI vs. MTU/S and CSAU/S: r = 0.90 and 0.96, respectively, both P < 0.0001) immobilization. The relationship between the methods was notably stronger for MG than TA at each time‐point (e.g., CSAMRI vs. MTU/S: MG, r = 0.70, P = 0.0006; TA, r = 0.37, P = 0.10). There was no relationship between the degree of DMA determined by the two methods in either muscle (e.g., TA pre‐ vs. post‐immobilization, VOLMRI: 136 ± 6 vs. 133 ± 5, P = 0.08; CSAU/S: 6.05 ± 0.3 vs. 5.92 ± 0.4, P = 0.70; relationship between methods: r = 0.12, P = 0.75). Conclusions Both MTU/S and CSAU/S provide comparable static measures of lower leg muscle size compared with MRI, albeit with weaker agreement in TA compared to MG. Although both MTU/S and CSAU/S can discern differences in DMA susceptibility between muscles, neither can reliably assess degree of DMA. Based on the growing recognition of heterogeneous atrophy profiles between muscles, and the topical importance of less commonly studied muscles (i.e., TA for falls prevention in older adults), future research should aim to optimize accessible methods to determine muscle losses across the body.